Pulmonary Hypertension in Patients with Heart Failure and Preserved Ejection Fraction: Differential Diagnosis and Management. (1st March 2016) - Hussain, Nehal; Charalampopoulos, Athanasios; Ramjug, Sheila; Condliffe, Robin; Elliot, Charlie A.; O'Toole, Laurence; Swift, Andrew; Kiely, David G
Abstract : The most common cause of pulmonary hypertension (PH) due to left heart disease (LHD) was previously rheumatic mitral valve disease. However, with the disappearance of rheumatic fever and an aging population, nonvalvular LHD is now the most common cause of group 2 PH in the developed world. In this review, we examine the challenge of investigating patients who have PH and heart failure with preserved ejection fraction (HF‐pEF), where differentiating between pulmonary arterial hypertension (PAH) and PH‐LHD can be difficult, and also discuss the entity of combined precapillary and postcapillary PH. Given the proven efficacy of targeted therapy for the treatment of PAH, there is increasing interest in whether these treatments may benefit selected patients with PH associated with HF‐pEF, and we review current trial data.